2011
DOI: 10.1038/nm.2315
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia susceptibility pathway neuregulin 1–ErbB4 suppresses Src upregulation of NMDA receptors

Abstract: Hypofunction of the N-methyl D-aspartate subtype of glutamate receptor (NMDAR) is hypothesized to be a mechanism underlying cognitive dysfunction in individuals with schizophrenia. For the schizophrenia-linked genes NRG1 and ERBB4, NMDAR hypofunction is thus considered a key detrimental consequence of the excessive NRG1-ErbB4 signaling found in people with schizophrenia. However, we show here that neuregulin 1β-ErbB4 (NRG1β-ErbB4) signaling does not cause general hypofunction of NMDARs. Rather, we find that, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 61 publications
13
150
1
Order By: Relevance
“…9A-C]. This observation is consistent with previous reports demonstrating a suppressive effect of mNRG-1 on LTP (Huang et al, 2000;Ma et al, 2003;Iyengar and Mott, 2008;Pitcher et al, 2008;Chen et al, 2010;Pitcher et al, 2011). By contrast, bath application of recombinant NRG-1 177-246 had no effect on basal synaptic strength in wild-type or neuropsin knock-out slices (see Fig.…”
Section: Impairment Of Gabaergic Inhibition In Neuropsin Knock-out Micesupporting
confidence: 91%
See 2 more Smart Citations
“…9A-C]. This observation is consistent with previous reports demonstrating a suppressive effect of mNRG-1 on LTP (Huang et al, 2000;Ma et al, 2003;Iyengar and Mott, 2008;Pitcher et al, 2008;Chen et al, 2010;Pitcher et al, 2011). By contrast, bath application of recombinant NRG-1 177-246 had no effect on basal synaptic strength in wild-type or neuropsin knock-out slices (see Fig.…”
Section: Impairment Of Gabaergic Inhibition In Neuropsin Knock-out Micesupporting
confidence: 91%
“…LTP was induced by a single tetanic stimulation, which consisted of 100 stimuli delivered at 100 Hz at the test intensity. Recombinant human NRG-1 EGF-like domain [NRG-1 177-246 , a functional NRG-1 (Bjarnadottir et al, 2007;Chen et al, 2010;Pitcher et al, 2011); the EGF-like domain consists exactly of amino acid residues 177-246] (Peprotech) was applied to slices at 0.5 or 10 nM for 20 or 35 min after a stable baseline had been attained. ACSF was also supplemented as indicated with AG1478 (5 M; LC Laboratories) or bicuculline methiodide (Bicu) (10 M; Santa Cruz Biotechnology).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in activity of the NRG1/ErbB3 signaling pathway also inhibits the Src kinase that is a regulator of the NMDAR. 19 Brain-derived neurotrophic factor (BDNF) and TrkB receptor dysfunction in schizophrenia. The expression of brainderived neurotrophic factor (BDNF) and its receptor TrkB are reduced in schizophrenia and this may have a major impact on the function of the inhibitory interneurons particularly during early development.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…As a result, we found that 59 candidate genes have been connected to SCZ [34][35][36][37][38], 77 candidate genes have been linked to T2D [39][40][41][42][43], while 25 candidate genes [44][45][46][47][48][49] have been implicated to both SCZ and T2D with various studies (Additional file 5). Totally, 161 candidate genes (~45% of all candidate genes) have been related to either SCZ or T2D or both diseases with various experimental approaches, further proving the rationale of "function association" in the application of disease related gene inference.…”
Section: New Candidate Risk Gene Inferencementioning
confidence: 90%